Testing the Asymmetric Relationship between Interest Rate and Inflation in Nigeria: An Empirical Analysis (NARDL) Approach - Shuaibu, Mukhtar; Ibrahim Musa; Abdulhamid, Jabir; Rabi’u, Sanusi (International Journal of Economic, Finance and Business Statistics, 2024)
The asymmetric relationship between interest rates and inflation in Nigeria is a complex issue that requires further investigation. The Nonlinear Auto Regressive Distributed Lag Model (NARDL) was used to examine this relationship using annual time series data The asymmetric relationship between interest rates and inflation in Nigeria is a complex issue that requires further investigation. The Nonlinear Auto Regressive Distributed Lag Model (NARDL) was used to examine this relationship using annual time series data from 1986 to 2023. The NARDL Bound test revealed cointegration among variables, with long-run coefficients indicating that a 1% increase in inflation leads to a -0.568 decrease in interest rates and a -0.483 increase in interest rates. The study also found that the short-run asymmetric effect of inflation to inflation decreases by (-.898) percent in the current period, while maintaining a decrease rate in subsequent periods. The ECM(-1) term satisfies the condition of its negative and statistical property of convergence from a long-run disequibrium. The study recommends tight monetary measures to avert inflationary tendencies during monetary crises and expansionary measures during recessions to curtail uncertainties. Governments should use inflation rates to service outstanding debts and address idle cash balances, fostering efficiency in the financial system through key indicators of interest rate and inflation. from 1986 to 2023. The NARDL Bound test revealed cointegration among variables, with long-run coefficients indicating that a 1% increase in inflation leads to a -0.568 decrease in interest rates and a -0.483 increase in interest rates. The study also found that the short-run asymmetric effect of inflation to inflation decreases by (-.898) percent in the current period, while maintaining a decrease rate in subsequent periods. The ECM(-1) term satisfies the condition of its negative and statistical property of convergence from a long-run disequibrium. The study recommends tight monetary measures to avert inflationary tendencies during monetary crises and expansionary measures during recessions to curtail uncertainties. Governments should use inflation rates to service outstanding debts and address idle cash balances, fostering efficiency in the financial system through key indicators of interest rate and inflation.